2018
DOI: 10.21031/epod.410287
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’deki Öğretmen Adaylarının Öğretmenlik Mesleğine Yönelik Tutumlarının Demografik Özelliklere Göre İncelenmesi: Bir Meta-Analiz Çalışması

Abstract: This research aims to explore whether prospective teachers' attitudes towards the teaching profession vary across demographic characteristics. A meta-analysis has been conducted for the related studies on prospective teachers' attitudes towards the teaching profession in Turkey. The effect sizes for random effects model have been employed over 103 studies in terms of gender, 26 regarding grade level, 18 for the presence of a teacher in the family, and 11 for the graduated faculties by using Hedges' g coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
8
0
2
Order By: Relevance
“…T of the studies examined as a result of the analysis explains that women exhibit a more positive attitude towards the teaching profession than men. Another similar meta-analysis study was done by Atalmış and Köse (2018). As a result of the analysis conducted with 106 studies containing gender variable, it was revealed that female teacher candidates have a more positive attitude.…”
Section: Discussionmentioning
confidence: 82%
“…T of the studies examined as a result of the analysis explains that women exhibit a more positive attitude towards the teaching profession than men. Another similar meta-analysis study was done by Atalmış and Köse (2018). As a result of the analysis conducted with 106 studies containing gender variable, it was revealed that female teacher candidates have a more positive attitude.…”
Section: Discussionmentioning
confidence: 82%
“…As a result of the meta-analysis study in which prospective teachers' attitudes towards teaching profession changed according to gender, grade level, the family status of being a teacher and the type of faculty that was taught/graduated, the results of the meta-analysis study showed that the female teacher candidates were more positive than the male teacher candidates. They are in the attitude of the statistical data that emerged (Atalmış & Köse, 2018). In the study, in which Musa and Bichi (2015) examined the teaching profession attitudes of preservice teachers and particularly preservice primary school teachers at the Northwest University in Nigeria, they reached a conclusion that the scores of the female preservice teachers were higher than those of the male preservice teachers, like in the study that was mentioned.…”
Section: Discussionmentioning
confidence: 84%
“…Second, empirical studies on prospective teachers revealed mixed findings of gender differences concerning the teaching profession. For instance, in their meta-analytic studies, Erdamar, Aytac, Turk, and Arseven (2016) and Atalmis and Kose (2018) concluded that the teacher candidates' attitudes towards the teaching profession were significantly higher in favor of females. However, while the selfefficacy of prospective teachers regarding certain teaching competencies was higher for males in some studies, no gender differences were reported in other studies (see in Yenice, 2012).…”
Section: Multicultural Competence and Its Dimensionsmentioning
confidence: 99%